A study on impact of PSL on gross NPAS of nationalised banks: an empirical approach - Susena, Karona Cahya; Huda, Miftachul; Maseleno, Andino; Sahoo, Bibhu Prasad; Kaur, Karman (Linguistics and Culture Review, 2021)
In order to encourage banks to lend more to neglected areas of the economy, the idea of a priority sector was introduced. These priority sectors add significantly to gross domestic product but have not received sufficient finance to function adequately. However, lending in the priority sector is not very warmly welcomed by the banks, particularly nationalized banks in India, as they generate more nonperforming assets than other sectors. It is the priority sector that contributes to the biggest default. As far as NPAs on account lending to the priority sector are concerned, it has been observed that there are inefficiencies in this sector, such that the fresh loans turning bad. Thus, our study examines the impact of non-priority sector loans on the rise of NPAs in the nationalized banks.